Discovery of a point-like very-high-energy γ-ray source in Monoceros - Funk, Stefan; van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2007)
Aims. The complex Monoceros Loop SNR/Rosette Nebula region contains several potential sources of very-high-energy (VHE) y-ray emission and two as yet unidentified high-energy EGRET sources. Sensitive VHE observations are required to probe acceleration processes in this region. Methods. The HESS telescope array has been used to search for very high-energy y-ray sources in this region. CO data from the NANTEN telescope were used to map the molecular clouds in the region, which could act as target material for γ-ray production via hadronic interactions. Results. We announce the discovery of a new y-ray source, HESS J0632+057, located close to the rim of the Monoceros SNR. This source is unresolved by HESS and has no clear counterpart at other wavelengths but is possibly associated with the weak X-ray source 1RXS J063258.3+054857, the Be-star MWC 148 and/or the lower energy γ-ray source 3EGJ0634+0521. No evidence for an associated molecular cloud was found in the CO data. © ESO 2007.
Keywords: Gamma rays: observations